Infectious diseases in the era of refugees: Hepatitis A outbreak in Lebanon - Abdul Rahman Bizri (Thieme Medical and Scientific Publishers Pvt. Ltd., 2018)
Background: The Syrian crisis has altered the epidemiology of infectious diseases in countries hosting large numbers of refugees. Lebanon witnessed several outbreaks linked to the presence of significant numbers of Syrian refugees, namely, Hepatitis A virus (HAV). We explore the epidemiology of HAV in Lebanon and the impact of the Syrian war during the 2014 outbreak and suggest solutions to prevent and minimize the HAV spread amid the current socioeconomic conditions. Methods: We reviewed all HAV cases reported to the Epidemiologic Surveillance Unit at the Ministry of Public Health between January 2001 and December 2017. Demographics and distribution of Syrian refugees in Lebanon were linked to reports of new HAV cases. Results: A sharp rise in the number of reported HAV cases was observed in Lebanon in 2013, concurrent with the Syrian crisis and influx of refugees. Most cases reported in 2013 and 2014 involved Syrian refugees and their relevant areas of settlement in the Beqaa and North governorates. Conclusion: The influx of refugees strained overburdened sanitary infrastructure and overstretched existing public health services in Lebanon, which led to an increase in the incidence of reported HAV cases. The Lebanese health authorities and the international community need to intensify their efforts in surveillance and prevention of communicable diseases. Providing proper sanitation and free vaccination for affected communities are effective solutions to contain the HAV outbreak. Yet, financial constraints and the need to prioritize in the health budget put HAV-immunization at a lower priority. The Lebanese scenario could be reflective to other countries hosting sizeable numbers of refugees.